PERSPECTIVE - Is there something exciting in today’s sedimentology? - Ricci Lucchi, Franco (Journal of Mediterranean Earth Sciences, 2014)
I present here some personal, and obviously biased thoughts and memories on the development of sedimentology during the last decades. My “tale” is limited to clastic sedimentology, the field of my personal experience, and is by no means exhaustive. I hope that other colleagues whose professional life has been more or less parallel to mine will do the same concerning, let’s say, carbonate deposits or provenance studies...